The Legal Protection Of Workers' Rights Fulfillment Of The Homeworker In The Industrial Relations Court Semarang - Siti Putri Indah Meilani (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The study on “The Legal Protection of Workers' Rights Fulfillment of The Homeworker In the Industrial Relations Court Semarang